The ice princess eaudiobook - Läckberg, Camilla (Fjällbacka, 2010)
Returning to her hometown after the funeral of her parents, writer Erica Falck finds a community on the brink of tragedy. The death of her childhood friend, Alex, is just the beginning. Her wrists slashed, her body frozen in an ice cold bath, it seems that she has taken her own life. Erica conceives a memoir about the beautiful but remote Alex, one that will answer questions about their lost friendship. While her interest grows to an obsession, local detective Patrik Hedstrom is following his own suspicions about the case. But it is only when they start working together that the truth begins to emerge about the small town with a deeply disturbing past.